CD80 Expression Correlates with IL-6 Production in THP-1-Like Macrophages Costimulated with LPS and Dialyzable Leukocyte Extract (Transferon®). (10th April 2019) - Jiménez-Uribe, Alexis P.; Valencia-Martínez, Hugo; Carballo-Uicab, Gregorio; Vallejo-Castillo, Luis; Medina-Rivero, Emilio; Chacón-Salinas, Rommel; Pavón, Lenin; Velasco-Velázquez, Marco A.; Mellado-Sánchez, Gabriela; Estrada-Parra, Sergio; Pérez-Tapia, Sonia M.
Abstract : Transferon® is a complex drug based on a mixture of low molecular weight peptides. This biotherapeutic is employed as a coadjuvant in clinical trials of several diseases, including viral infections and allergies. Given that macrophages play key roles in pathogen recognition, phagocytosis, processing, and antigen presentation, we evaluated the effect of Transferon® on phenotype and function of macrophage-like cells derived from THP-1 monocytes. We determined the surface expression of CD80 and CD86 by flow cytometry and IL-1 β, TNF- α, and IL-6 levels by ELISA. Transferon® alone did not alter the steady state of PMA-differentiated macrophage-like THP-1 cells. On the contrary, simultaneous stimulation of cells with Transferon® and LPS elicited a significant increase in CD80 (P ≤ 0.001 ) and CD86 (P ≤ 0.001 ) expression, as well as in IL-6 production (P ≤ 0.05 ) compared to the LPS control. CD80 expression and IL-6 production exhibited a positive correlation (r = 0.6, P ≤ 0.05 ) in cells exposed to Transferon® and LPS. Our results suggest that the administration of Transferon® induces the expression of costimulatory molecules and the secretion of cytokines in LPS-activated macrophages. Further studies are necessary to determine the implication of these findings in the therapeutic properties of Transferon®.